2023
DOI: 10.1088/2516-1075/acfa4e
|View full text |Cite|
|
Sign up to set email alerts
|

Progress in the studies of electronic and magnetic properties of layered MPX3 materials (M: transition metal, X: chalcogen)

Yuriy Dedkov,
Yefei Guo,
Elena Voloshina

Abstract: The recent progress in the studies of 2D materials placed in front many experimental and theoretical works on the interesting class of materials, the so-called transition metal phosphorus trichalcogenides with structural formula MPX3 (M: transition metal, X: chalcogen). Here, the diversity in the M/X combination opens the possibility to tune the electronic and magnetic properties of these materials in a very wide range, resulting in many interesting physical phenomena followed by the promoting their use in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 136 publications
0
17
0
Order By: Relevance
“…These materials are also considered as a 3D basis for the preparation of their 2D counterpart in the form of mono- and multilayers. Among them, transition metal dichacogenides (MX 2 ; M = transition metal, X = chalcogen) and phosphorus trichalcogenides (MPX 3 ) , are the focus of many experimental and theoretical works, giving much hope for application in different areas. The mentioned transition-metal phosphorus trichalcogenides with a structural formula MPX 3 have a layered structure and crystallize within either the C 2/ m (X = S) or R 3̅ (X = Se) space group. ,, Every single layer is built on the basis of the honeycomb lattice formed by M 2+ ions, where every hexagon is centered by the P–P dimer forming the [P 2 X 6 ] 4– bipyramid with chalcogen layers sandwiching the layer of M 2+ ions, as shown in Figure a. The diversity in the M/X combination gives a wide range for band gaps and different magnetic configurations of MPX 3 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…These materials are also considered as a 3D basis for the preparation of their 2D counterpart in the form of mono- and multilayers. Among them, transition metal dichacogenides (MX 2 ; M = transition metal, X = chalcogen) and phosphorus trichalcogenides (MPX 3 ) , are the focus of many experimental and theoretical works, giving much hope for application in different areas. The mentioned transition-metal phosphorus trichalcogenides with a structural formula MPX 3 have a layered structure and crystallize within either the C 2/ m (X = S) or R 3̅ (X = Se) space group. ,, Every single layer is built on the basis of the honeycomb lattice formed by M 2+ ions, where every hexagon is centered by the P–P dimer forming the [P 2 X 6 ] 4– bipyramid with chalcogen layers sandwiching the layer of M 2+ ions, as shown in Figure a. The diversity in the M/X combination gives a wide range for band gaps and different magnetic configurations of MPX 3 .…”
mentioning
confidence: 99%
“…The diversity in the M/X combination gives a wide range for band gaps and different magnetic configurations of MPX 3 . Following many experimental and theoretical works, MPX 3 are wide band gap antiferromagnetic (AFM) materials (band gaps spread in the range 1.2–3.5 eV), ,, where coupling between M 2+ magnetic moments is determined according to the Goodenough–Kanamori rule. However, it was found that magnetic configurations and coupling strength between these magnetic moments can be tuned using adsorption or intercalation of different materials, by doping or alloying, thus opening perspectives for the application of these materials in spintronics and optical sensing. With respect to the studies of the electronic structure of MPX 3 , the existence of three different interactions in these materialsionic, covalent, and vdWmakes the description of the electronic structure of MPX 3 a very interesting and challenging task …”
mentioning
confidence: 99%
See 3 more Smart Citations